Cyanobacterial bloom associated with a complete turnover of a Daphnia population in a warm‐temperate eutrophic lake in Eastern China. (2nd December 2021) - Ma, Xiaolin; Deng, Zhixiong; Blair, David; Bi, Yonghong; Hu, Wei; Yin, Mingbo
Abstract: The effect of cyanobacterial blooms on aquatic ecosystems has received wide attention, yet little is known about their impacts on zooplankton genetic structure. For 26 months (April 2012–May 2014), we monitored zooplankton in a warm‐temperate ice‐free lake in Eastern China, with an emphasis on seasonal population dynamics of the cladoceran, Daphnia galeata . There was a seasonal succession in the zooplanktonic community (composed of Cladocera, Copepoda, and Rotifera). Genetic analysis (based on 14 microsatellite loci) of the 21 monthly samples in which D. galeata was present demonstrated that several clones could successfully overwinter and/or persist for many months. However, all clones, including these long‐lived clones, were completely replaced by new ones after October 2013, probably due to cyanobacteria blooms in that summer. A high clonal richness coupled with high turnover rate was observed in the D .  galeata population overall, suggesting frequent sexual reproduction. Daphnia galeata experimentally fed with a diet of Microcystis aeruginosa (the most abundant toxic cyanobacterial species in the lake) had a substantially reduced survivorship, consistent with the field observations. Our findings highlight the changes of zooplanktonic population dynamics in terms of both community and clonal structure in a warm‐temperate ice‐free lake, and call for further investigation on ecological responses of zooplankton to cyanobacterial blooms.